Ethanolic Extract of Xestospongia Sp. Induces CD4+ and CD14 Cells Levels on Wistar Male Rat Infected with Staphylococcus aureus - Adryan Fristiohady; Wahyuni Wahyuni; Muhammad H Malaka; Dewiyanti Madu; Dayatriana Muthalib; Dian Munasari; La Ode MJ Purnama; Baru Sadarun; Muhammad Ilyas; Idin Sahidin (Pharmacology and Clinical Pharmacy Research)
Immunomodulator is a substance that increases or suppresses the immune response through the certain mechanism. The marine sponge Xestospongia sp. has immunomodulatory activity by increasing phagocytic activity. In addition, the phagocytic activity is affected by CD4+ and CD14 cells levels. Thus, this study aims to investigate the effect of Xestopongia sp. extract toward CD4+ and CD14 cells level in model rat. Animals were divided into 4 groups (n=5) and treated for 7 days, as follow: Group I (Ethanolic extract of Xestospongia sp. dose of 300 mg/KgBW); Group II (Ethanolic extract of Xestospongia sp. dose of 400 mg/KgBW); Group III (Phylantus niruri extract); and Group IV (0.5% Na CMC). On day 8, animals were infected with Staphylococcus aureus intraperitoneally. And the blood was collected by cardiac puncture and assayed with ELISA kit CD4 (elabscience®) and ELISA kit CD14 (elabscience®). Ethanolic extract of Xestospongia sp. provided high levels of both CD4+ and CD14 cells (Group II) compared to baseline (Group IV)  (p<0.05). Group I provided similar activity to group III (p>0.05) and Group II provided significant activity with higher levels of CD4+ and CD14 cells compared to group III (p<0.05). In conclusion, both doses of Xestospongia sp. extract provide activity as immunomodulator by increasing CD4+ and CD14 cells levels, yet dose of 400 mg/KgBw provides the higher immunomodulatory activity.